Virtual Reality Technology and Remote Digital Application for Tele-Simulation and Global Medical Education: An Innovative Hybrid System for Clinical Training. (October 2021) - Almousa, Omamah; Zhang, Ruby; Dimma, Meghan; Yao, Jieming; Allen, Arden; Chen, Leo; Heidari, Parastou; Qayumi, Karim
Objective: Althoughsimulation -based medical education is fundamental for acquisition and maintenance of knowledge and skills; simulators are often located in urban centers and they are not easily accessible due to cost, time, and geographic constraints. Our objective is to develop a proof-of-concept innovative prototype usingvirtual reality (VR) technology for clinicaltele simulation training to facilitate access and global academic collaborations. Methodology: Our project is aVR- based system using Oculus Quest as a standalone, portable, and wireless head-mounted device, along with a digital platform to deliver immersive clinical simulation sessions. Instructor's control panel (ICP) application is designed to createVR -clinical scenarios remotely, live-stream sessions, communicate with learners and control VR-clinical training in real-time. Results: TheVirtual Clinical Simulation (VCS) system offers realistic clinical training in virtual space that mimics hospital environments. ThoseVR clinical scenarios are customizable to suit the need, with high-fidelity lifelike characters designed to deliver interactive and immersive learning experience. The real-time connection and live-stream between ICP andVR- training system enables interactive academic learning and facilitates access totele simulation training. Conclusions: VCS system provides innovative solutions to major challenges associated with conventional simulation training such as access, cost, personnel, and curriculum.VCS facilitates the delivery of academic and interactive clinical training that is similar to real-life settings.Tele- clinical simulation systems likeVCS facilitate necessary academic-community partnerships, as well as global education network between resource-rich and low-income countries.